Marsirimpa Tradition as a Livelihood Strategy of Sharecroppers in Sidiangkat Village, Sidikalang District - Sianturi, Lisbet Rizona Br; Ginting, Bengkel (Journal of Peasants' Rights, 2024)
The marsirimpa tradition is a survival strategy carried out by poor farmers, one of which is rice farming sharecroppers in Sidiangkat Village, Sidikalang District. This strategy is carried out to minimize the amount of expenditure on capital for agricultural activities. The poverty experienced by sharecroppers which can be seen based on the socio-economic conditions of the family affects the survival strategy carried out. This means that the marsirimpa tradition is carried out by poor farmers who have limited capital. This research aims to describe the socio-economic conditions and survival strategies carried out by sharecroppers in SidiangkatVillage in meeting family needs. The main informant in this research is the head of Sidiangkat neighborhood I, the main informant is four sharecroppers, additional informants are two landowners. Data collection techniques are done by literature study, interviews, observation and documentation. The data obtained in the field was then analyzed qualitatively to produce a conclusion. The results showed that the socio-economic conditions of sharecroppers were below the poverty line with a total income of around Rp500,000 to Rp1,000,000 per month with two to six dependents. The type of residence is contact and self-owned which is equipped with a PLN lighting source and well and irrigation water sources and has been facilitated with private toilets. Active strategies carried out are by increasing income, having additional jobs, raising livestock and utilizing the potential of family members. Passive strategies by minimizing expenses or implementing savings strategies. While the network strategy is carried out by making loans, utilizing government assistanceand assistance from relatives.